Challenges and Transformation: Revealing the Dynamics of Socio-Cultural Change in the Modern Era - Wahyu Mukti, Muhammad Panji; Wadiyo, Wadiyo; Supriyanto, Teguh (JURNAL PAKARENA, 2024)
Socio-cultural changes in Indonesian society in the modern era face various complex and dynamic challenges. Globalization, information technology, and higher mobility have profoundly changed the socio-cultural landscape. The purpose of this research is to highlight the complexity of challenges and transformations in revealing the dynamics of socio-cultural changes in Indonesian society in the modern era. The research method used is a literature study, namely by solving problems by tracing the sources of writings that have been made before. The results show that one of the main challenges is preserving traditional values and local culture amid the influence of globalization. The urge to adopt lifestyles, values, and norms from foreign cultures often conflicts with local values. In addition, rapidly developing information technology also brings new challenges in the form of changing patterns of communication, social interaction, and cultural identity. However, Indonesian society is also undergoing a significant transformation in the face of these challenges. Increasingly accessible education allows for increased awareness and understanding of local cultural values. Technological innovations are also used to preserve cultural heritage through various media. In addition, the spirit of gotong royong and togetherness that characterizes Indonesian society remains strong, despite the pressures of socio-cultural change. Communities are adapting to new ways of maintaining traditional values while embracing the positive aspects of globalization.